Perancangan Augmented Reality Berbasis Android Menggunakan Metode Mdlc Dengan Algoritma Surf - Ramadhan, Rizky; Khalida, Rakhmi; Setiawati, Siti; Lubis, Hendarman (Journal of Information System, Informatics and Computing; Vol 8 No 2 (2024): JISICOM (July-December 2024)DO - 10.52362/jisicom.v8i2.1714, 2024)
Public awareness of traditional West Javanese musical instruments is still limited, resulting in the loss of cultural identity, the decline of traditional music, and the weakening of national spirit, innovation, and economic potential. This research aims to overcome these problems by developing an interactive smartphone application that introduces and preserves the musical heritage of West Java. Using the Multimedia Development Life Cycle(MDLC) method with the stages of Concept, Design, Material Collecting, Assembly, Testing, this AR application integrates the Speeded-Up Robust Features Algorithm for marker recognition, by ensuring robust image processing stages such as Integral Image, Grayscale conversion, Interest Point Detection, and Feature Matching. The InmusWJ AR application successfully introduced eight pages including the main menu, music list, application information, five AR camera pages, and menu buttons. This application displays 3D models of five traditional musical instruments (angklung, calung, celempung, kecapi, tarawangsa) along with their cultural background. Testing on markers with 10%, 30%, and 50% scratches shows that the marker can be read and is able to display 3D objects of musical instruments. and testing with 20% and 50% closed markers can be read and display objects, but cannot be read when the marker is 100% closed.